2018
DOI: 10.1136/jnnp-2017-317371
|View full text |Cite
|
Sign up to set email alerts
|

Interrogating cortical function with transcranial magnetic stimulation: insights from neurodegenerative disease and stroke

Abstract: Transcranial magnetic stimulation (TMS) is an accessible, non-invasive technique to study cortical function in vivo. TMS studies have provided important pathophysiological insights across a range of neurodegenerative disorders and enhanced our understanding of brain reorganisation after stroke. In neurodegenerative disease, TMS has provided novel insights into the function of cortical output cells and the related intracortical interneuronal networks. Characterisation of cortical hyperexcitability in amyotrophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 184 publications
1
23
0
Order By: Relevance
“…The classic drug design approach is aimed at developing a drug that targets a single protein or signaling pathway for the treatment of disease [37]. However, many neurological diseases such as stroke and neurodegenerative diseases may require multiple treatments due to their complexity [38]. In this study, we found that metformin exerts neuroprotective effects on I/R injury induced by OGD/R or MCAO/R.…”
Section: Discussionmentioning
confidence: 74%
“…The classic drug design approach is aimed at developing a drug that targets a single protein or signaling pathway for the treatment of disease [37]. However, many neurological diseases such as stroke and neurodegenerative diseases may require multiple treatments due to their complexity [38]. In this study, we found that metformin exerts neuroprotective effects on I/R injury induced by OGD/R or MCAO/R.…”
Section: Discussionmentioning
confidence: 74%
“…The second point to make is that we found no strong clinical indicators, among our measured explanatory variables, of which patients were most likely to change, including sensory loss in the hand, fatigue25 and depression (tables 4 and 5). It might be that neurophysiological (presence or absence of motor evoked potentials),26 neuroimaging (assessment of corticospinal tract, whole brain damage or brain function)27–30 or cognitive (sustained attention, memory, motivation)31 32 measures are required for accurate stratification based on likely response, and this can certainly be tested in future.…”
Section: Discussionmentioning
confidence: 99%
“…The cortex of HD mutation carriers shows progressive regional thinning in a topographically predictable manner already up to 15 years before the onset of motor symptoms (Rosas et al, 2005(Rosas et al, , 2008Nopoulos et al, 2010). On a functional level, one of the earliest events in HD is increased cortical excitability and impaired GABA-mediated cortical inhibition, as shown by transcranial magnetic stimulation studies already in the presymptomatic phase of the disease (Nardone et al, 2007;Schippling et al, 2009;Philpott et al, 2016;Agarwal et al, 2019).…”
Section: Cortical Circuitsmentioning
confidence: 99%